A Sensitivity Analysis to Assess Bias Due to Selecting Subjects Based on Treatment Received. Issue 2 (March 2016) - Ertefaie, Ashkan; Small, Dylan; Flory, James; Hennessy, Sean
Abstract : Supplemental Digital Content is available in the text.